2013
DOI: 10.1039/c3tb20859a
|View full text |Cite
|
Sign up to set email alerts
|

Fe doped CdTeS magnetic quantum dots for bioimaging

Abstract: A facile synthesis of 3-6 nm, water dispersible, near-infrared (NIR) emitting, quantum dots (QDs) magnetically doped with Fe is presented. Doping of alloyed CdTeS nanocrystals with Fe was achieved in situ using a simple hydrothermal method. The magnetic quantum dots (MQDs) were capped with NAcetyl-Cysteine (NAC) ligands, containing thiol and carboxylic acid functional groups to provide stable aqueous dispersion. The optical and magnetic properties of the Fe doped MQDs were characterized using several technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…The N1s spectrum ( Figure 4d) was resolved into two peaks at 399.8 and 401.2 eV. These peaks corresponded to C-N-C and (C)3-N bonds, respectively [19,20]. The experimental results were consistent with the FT-IR characterisation [21,22].…”
Section: Characterisation Of Stc-npssupporting
confidence: 80%
“…The N1s spectrum ( Figure 4d) was resolved into two peaks at 399.8 and 401.2 eV. These peaks corresponded to C-N-C and (C)3-N bonds, respectively [19,20]. The experimental results were consistent with the FT-IR characterisation [21,22].…”
Section: Characterisation Of Stc-npssupporting
confidence: 80%
“…Saha et al reported Fe doped CdTeS quantum dots capped with N -acetyl-cysteine (NAC) ligands. 57 Due to the concern about potential leakage of highly toxic cadmium ions, researchers have attempted to synthesis non-cadmium based QD (e.g., ZnO, [58][59][60] ZnS, 61 62 InP, 63 64 CuInS 2 65 ), and many of those QDs are also used to produce multimodality probes. Lin et al reported a CuInS 2 /Zn 1−x Mn x S Core/Shell QDs.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Since Schwartz et al reported the synthesis of Co 2+ and Ni 2+ doped ZnO nanocrystals in 2003, [30] more and more magnetic ions doped QDs have been prepared as dual-modal agents in the last two decades, such as Ni-doped CdTeSe/CdS, [31] Fe-doped CdTeS, [32] Gd-doped CdSe, [27] Mn-doped CdSe, [33], Mn-doped CdS/ZnS [34], Gd-doped ZnO [29], Gd-doped ZnAgInS 3 [35] and Gd-doped CuInS/ZnS [36]. However, most of these magnetic QDs were prepared in organic phase and further surface modifications were necessary to make them water -soluble, which are time-consuming and always lead to the decrease of quantum yields.…”
Section: Introductionmentioning
confidence: 99%